"The Brain" - The Philological Library, Free University of Berlin - Werner, Klaus U.; Diecks, Monika (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
In 1997 Lord Norman Foster was commissioned to design a new library building to house the 10 previously separate departmental librariesof the Faculty of Philosophy and Humanities. The new library had to be integrated into the existing Free University building of 1971, which would simultaneously undergo a comprehensive refurbishment. The 'Rostlaube' ('rusty shack') is a typical example of late sixties architecture. It was designed by Candilis, JosicandWoods in a modular griddling system influenced by Le Corbusier. The entire structure now has to be stripped of asbestos, the worn-out façade needs a facelift and the technical infrastructure must be updated to meet present standards. As far as the reconstruction is concerned, Foster has opted to preserve the original state where possible and keep alterations to a minimum. The library is a completely new component, though, for which parts of the existing building had to be removed. The erection of a new library building was necessitated by the intention of bringing together within the 'Rostlaube' 10 separate departments, currently spread all over campus, together with their staff and administrative offices as well as lecture-rooms. At the same time, the departmental libraries are to be integrated into one, which is a completely new departure for the Free University. The collections of the Philological Library cover classical and modern languages and literatures as well as comparative literature and linguistics. The new building will have a capacity of 800,000 volumes on open shelves and desk space for 650 readers. A state-of-the-art energy-saving heating system is included in the overall budget of 18 million Euros, while the cost of shelves and computer equipment is excluded.